An Adjuvanted, Postfusion F Protein–Based Vaccine Did Not Prevent Respiratory Syncytial Virus Illness in Older Adults. (23rd September 2017) - Falloon, Judith; Yu, Jing; Esser, Mark T; Villafana, Tonya; Yu, Li; Dubovsky, Filip; Takas, Therese; Levin, Myron J; Falsey, Ann R
Abstract : In a randomized, placebo-controlled, phase 2b clinical trial, an adjuvanted vaccine containing the respiratory syncytial virus (RSV) fusion protein was immunogenic but did not protect older adults from disease caused by RSV. Abstract: Background: Respiratory syncytial virus (RSV) is an important cause of illness in older adults. This study assessed efficacy of a vaccine for prevention of RSV-associated acute respiratory illness (ARI), defined by specified symptoms with virologic confirmation. Methods: This phase 2b study evaluated RSV postfusion F protein (120 µg) with glucopyranosyl lipid adjuvant (5 µg) in 2% stable emulsion. Subjects aged ≥60 years were randomly assigned at a ratio of 1:1 to receive vaccine or placebo (all received inactivated influenza vaccine). Ill subjects recorded symptoms and provided blood and nasal swab samples. Results: In the per-protocol population (n = 1894), the incidence of RSV-associated ARI occurring ≥14 days after dosing was 1.7% and 1.6% in the vaccine and placebo groups, respectively, for a vaccine efficacy (VE) of –7.1% (90% confidence interval [CI], –106.9%–44.3%). Efficacy was not observed in secondary analyses that included seroresponse to nonvaccine RSV antigens (VE, 8.9%; 90% CI, –28.5%–35.4%) or symptoms combined with seroresponse (VE, 10.0%; 90% CI, –45.4%–44.4%). On day 29, 92.9% of vaccinees had an anti-F immunoglobulin G antibody seroresponse. Overall, 48.5% and 30.9% of RSV vaccine recipients reported local and systemic solicited symptoms, respectively. Conclusion: The RSV vaccine was immunogenic but did not protect older adults from RSV illness. Clinical Trials Registration: NCT02508194.